Driving change travel in the twenty-first century - Metz, David (Agenda Publishing, 2023)
Over recent decades, the UK's transport system has undergone radical changes as a result of increased investment, the growth of population centres and technological advancements. In this book, David Metz examines the role new business models and government policies have played in these changes, highlighting many of the unforseen consequences for transport development and for future outcomes